If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3d+1)=3(d-2)
We move all terms to the left:
2(3d+1)-(3(d-2))=0
We multiply parentheses
6d-(3(d-2))+2=0
We calculate terms in parentheses: -(3(d-2)), so:We get rid of parentheses
3(d-2)
We multiply parentheses
3d-6
Back to the equation:
-(3d-6)
6d-3d+6+2=0
We add all the numbers together, and all the variables
3d+8=0
We move all terms containing d to the left, all other terms to the right
3d=-8
d=-8/3
d=-2+2/3
| 6y=5-y | | 69m-45+5(-3m-3)=15m-30m | | 1-3b=-2b+10 | | -f+7=42 | | (x+2)+(2x+1)=180 | | 13.7v-6.5=2.3v+8 | | 3(6n-7)+26=18(n+1) | | 5n-2n=42 | | -5(4t-4)+2t=5t-6 | | 3(c-4)=c+20 | | 14/3p-41/3p+2/6=51/8 | | 6(3n+5)=9(4n+7)+3 | | 3y+9=2y+-8 | | -5(-4x+8)=11 | | 14/3p-41/3p+2/6=751/8 | | 5(p-3)-2(p-3)=9 | | 3(-6x-9)=-8 | | 5x−8=−2 | | -4+9t=6t-7 | | 1/2(p+1)+3p=2/3p+3 | | -0.3x+0.6=-0.9-0.5x | | x/6=120/80 | | |4x+1|=|8x+3| | | (4x+1)+(2x+17)=180 | | (2s-1)2-225=0 | | x^2=49 | | 5-2x+8=3(2x+3) | | 8+8=-2(9x-8) | | 4x+1=8×+3 | | 12x²=17x-6 | | x²+12x=45 | | 2(k-5)=2k+5 |